AKAD MUDHARABAH SEBAGAI INSTRUMEN PENDANAAN DAN PEMBIAYAAN DI LEMBAGA KEUANGAN SYARIAH - Asep Dadang Hidayat; Mohamad Sar’an (Faculty of Sharia and Law, Sunan Gunung Djati Islamic State University of Bandung, 2020)
Abstract: Islamic financial institutions grow and develop in Indonesia in line with regulations issued by the government after the promulgation of Law no. 21 of 2008 concerning Islamic Banking. This study aims to discuss the Mudharabah Instrument agreement as Funding and Financing in Islamic Financial Institutions. This research includes using normative juridical methods and qualitative approaches. Data sources refer to books, documents, and other relevant written sources. The results of this study indicate that although mudharabah is not explicitly presented in the Al-Qur'an and As-Sunnah, most of the scholars are considered as the operational foundation of Islamic financial institutions. However, the development of the Mudharabah Akad Concept in Islamic Financial Institutions is still needed by the concept of modern economic development.